An insight into seasonal variations in food waste characteristics and associated carbon footprint management - Nithin Raja Cherukuri; Purushothaman Parthasarathy (Kuwait Journal of Science)
The abundant stockpiling of food waste (FW) which leads to climate change has been a growing concern over its carbon footprint (CF) in recent years. In India, student enrollment in higher education has been increasing in recent years, reaching close to 4 billion, especially in universities. The present study aims to identify varying characteristics of FW generated in a university hostel mess due to temporal and seasonal conditions. This study evaluates consumer attitudes and behaviors concerning FW, and artificial neural networks are also used to forecast the percentage of FW streams based on various characteristics. FW characters were found to vary with time and temperature. High moisture content during autumn and winter seasons was found to decrease destructible solids content, a key parameter governing biogas generation. Statistical assay of FW quantity shows that FW generation is high during the weekdays followed by Saturdays, whereas during festivals and Sundays, the generation is highly variable, which might be due to the presence of inmates during holidays. Based on data from six months sample data set, it is projected that 716.57 ​kgs of food were wasted per day with 1361.48 ​kgs carbon dioxide equivalent (CO2 eq.) related CF. It showed that parameters such as household wealth, meal contentment, meal days, education, sex, and food-saving efforts significantly impacted the CF of FW. The avoidable FW can be stopped nonetheless to prevent shadowed CF. It can be concluded that effective FW management can be done by varying number of collection points, where FW accumulation varies in a year, enabling an efficient source sorting process. This will help in transferring the FW to proper treatment and management process like anaerobic digestion and composting. The Anaerobic digestion pose an efficient methods of FW management due to its high potency in biogas production.